Bridging the gap in the knowledge of anatomy as a doctor journeys through the postgraduate medical training - David, Pamela; Zulkafli, Intan Suhana; Wong, Kah Hui; Samberkar, Snehlata Prashant; Naidu, Murali; Zamin, Rasheeda Mohd (2017)
The discipline of Anatomy is incorporated in the first undergraduate year of a Medical curriculum and is considered the cornerstone of Medical Education. Traditionally, Gross Anatomy was taught using real human body through cadaver dissection. However, curricula involving Anatomy has undergone a large paradigm shift due to various constraints. This study aims to explore the levels of knowledge in Human Anatomy in postgraduate students coming from diverse backgrounds and whether the knowledge can be improved in those lacking as they undergo postgraduate Medical Training. Their perceptions on postgraduate anatomy teaching and learning was also studied. Sampling included registered postgraduate students on voluntary basis. Questionnaire survey was disseminated to the postgraduate students in the beginning of the course, which gained us an understanding on the type of medical training received; and a preliminary test on the level of Anatomical knowledge was assessed. At the end of the usual lectures, brief demonstrations was conducted in the Dissection Hall. Students were then divided into 2 groups; one that is not exposed to any Intervention (Control group) and the other group that is exposed to Intervention (Intervention group). The intervention received was in the form of additional exposure to e-learning/dissection videos to enhance their understanding. Finally, all students were subjected to a Post-Test which determines if the intervention was effective. Overview of the data obtained demonstrated that the students appear to benefit from the intervention employed, with the Intervention group scoring a higher mean (62%) compared to the control group which had a mean score of 52%. Data from reflective session revealed that 82% of the postgraduate students from the intervention group gave positive evaluation regarding the intervention received and they felt that a thorough understanding of Human Anatomy is very essential, therefore having had the intervention session was more effective at aiding their learning and understanding. The findings from this study suggest that intervention such as e-learning/video can help bridge the gap in anatomy knowledge in the postgraduate trainee.